Indications for MARS-MRI in Patients Treated With Metal-on-Metal Hip Resurfacing Arthroplasty - Connelly, James W.; Galea, Vincent P.; Matuszak, Sean J.; Madanat, Rami; Muratoglu, Orhun; Malchau, Henrik (The Journal of arthroplasty, 2018)
Currently, there are no universally accepted guidelines on when to obtain metal artifact reduction sequence magnetic resonance imaging (MARS-MRI) in metal-on-metal (MoM) hip resurfacing arthroplasty (HRA) patients. Our primary aims were to identify which patient and clinical factors are predictive of adverse local tissue reaction (ALTR) and create an algorithm for indicating MARS-MRI in patients with Articular Surface Replacement (ASR) HRA. The secondary aim was to compare our algorithm to existing guidelines on when to perform MARS-MRI in MoM HRA patients. The study cohort consisted of 182 patients with unilateral ASR HRA from a prospective, multicenter study. Subjects received MARS-MRI at a mean of 7.8 years from surgery, regardless of symptoms. We determined which variables were predictive of ALTR and generated cutoffs for each variable. Finally, we created an algorithm to predict ALTR and indicate MARS-MRI in ASR HRA patients using these cutoffs and compared it to existing guidelines. We found high blood cobalt (Co) (odds ratio = 1.070; P = .011) and high blood chromium (Cr) (odds ratio = 1.162; P = .002) to be significant predictors of ALTR presence. Our algorithm using a blood Co cutoff of 1.15 ppb and a Cr cutoff of 1.09 ppb achieved 96.6% sensitivity and 35.3% specificity in predicting ALTR, which outperformed the existing guidelines. Blood Co and Cr levels are predictive of ALTR in ASR HRA patients. Our algorithm considering blood Co and Cr levels predicts ALTR in ASR HRA patients with higher sensitivity than previously established guidelines.